A large abdominal desmoid tumour associated with pregnancy and puerperium - Rathod, Setu; Samal, Sunil Kumar; Mahapatra, Purna Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
We report a rare case of huge abdominal desmoid tumour first detected during pregnancy. The patient delivered vaginally and the size of the tumour increased during puerperium for which resection was done. Most of these tumours occur in the abdominal muscles particularly right rectus abdominis, perhaps related to trauma from abdominal stretching and movement. These tumours are known to regress spontaneously after delivery which was not in our case. Subsequent pregnancies do not appear to result in recurrence in either FAP (Familial Adenomatous Polyposis) or non-FAP patients. It is not clear from currently available data whether pregnancy associated desmoids are molecularly distinct from other desmoids.